2016
DOI: 10.1002/ab.21637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the cyberbullying prevention program media heroes (Medienhelden) on traditional bullying

Abstract: There is considerable debate over whether cyberbullying is just another form of bullying, or whether it is a problem distinct enough to require specific intervention. One way to explore this issue is to analyze whether programs designed to prevent traditional bullying help prevent cyberbullying, and whether programs designed to prevent cyberbullying prevent traditional bullying. The main goal of the current study was to analyze the spillover effects of the cyberbullying prevention program Media Heroes (Medienh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 51 publications
(55 reference statements)
3
46
0
4
Order By: Relevance
“…However, the effects were only short-term. In a program called Media Heroes 722 students were assigned to a long intervention (15 sessions) or a short program (1 day) [56]. The program was designed to give bystanders strategies to defend victims from being cyberbullied by promoting empathy and knowledge of risks and consequences of cyberbullying.…”
Section: Bystandersmentioning
confidence: 99%
“…However, the effects were only short-term. In a program called Media Heroes 722 students were assigned to a long intervention (15 sessions) or a short program (1 day) [56]. The program was designed to give bystanders strategies to defend victims from being cyberbullied by promoting empathy and knowledge of risks and consequences of cyberbullying.…”
Section: Bystandersmentioning
confidence: 99%
“…Systematic reviews on bullying interventions showed that to date few programs existed that target cyberbullying (Cantone et al, 2015;Mishna, Cook, Saini, Wu, & MacFadden, 2011;Van Cleemput et al, 2013), and that effects were often limited to increasing Internet safety knowledge (Mishna et al, 2011). Since these reviews, however, several new intervention and prevention studies against cyberbullying among adolescents have been published (Chaux, Velasquez, Schultze-Krumbholz, & Scheithauer, 2016;Cross et al, 2016;Del Rey, Casas, & Ortega, 2016;Gradinger, Yanagida, Strohmeier, & Spiel, 2016;Palladino, Nocentini, & Menesini, 2016;Schultze-Krumbholz, Schultze, Zagorscak, W€ olfer, & Scheithauer, 2016). All these studies showed significant reductions in cyberbullying involvement despite variations in design and focus.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies showed significant reductions in cyberbullying involvement despite variations in design and focus. The design of these studied interventions varied from extensive school-based programs (Chaux et al, 2016; and whole-school programs (Cross et al, 2016;Del Rey et al, 2016;Gradinger et al, 2016) to peer-led education programs (Palladino et al, 2016). Some focused mainly on traditional bullying (Gradinger et al, 2016), others on cyberbullying (Chaux et al, 2016;Cross et al, 2016;Del Rey et al, 2016;, and some on both (Palladino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations